Assessment of short-term effects of thoracic radiotherapy on the cardiovascular parasympathetic and sympathetic nervous systems - Wu, Shuang; Guan, Weizheng; Zhao, Huan; Li, Guangqiao; Zhou, Yufu; Shi, Bo; Zhang, Xiaochun (Frontiers in Neuroscience, 2023)
Background Prior research suggests that cardiovascular autonomic dysfunction might be an early marker of cardiotoxicity induced by antitumor treatment and act as an early predictor of cardiovascular disease-related morbidity and mortality. The impact of thoracic radiotherapy on the parasympathetic and sympathetic nervous systems, however, remains unclear. Therefore, this study aimed to evaluate the short-term effects of thoracic radiotherapy on the autonomic nervous system, using deceleration capacity (DC), acceleration capacity (AC) of heart rate, and heart rate variability (HRV) as assessment tools. Methods A 5 min electrocardiogram was collected from 58 thoracic cancer patients before and after thoracic radiotherapy for DC, AC, and HRV analysis. HRV parameters employed included the standard deviation of the normal-normal interval (SDNN), root mean square of successive interval differences (RMSSD), low frequency power (LF), high frequency power (HF), total power (TP), and the LF to HF ratio. Some patients also received systemic therapies alongside radiotherapy; thus, patients were subdivided into a radiotherapy-only group (28 cases) and a combined radiotherapy and systemic therapies group (30 cases) for additional subgroup analysis. Results Thoracic radiotherapy resulted in a significant reduction in DC (8.5 [5.0, 14.2] vs. 5.3 [3.5, 9.4], p = 0.002) and HRV parameters SDNN (9.9 [7.03, 16.0] vs. 8.2 [6.0, 12.4], p = 0.003), RMSSD (9.9 [6.9, 17.5] vs. 7.7 [4.8, 14.3], p = 0.009), LF (29 [10, 135] vs. 24 [15, 50], p = 0.005), HF (35 [12, 101] vs. 16 [9, 46], p = 0.002), TP (74 [41, 273] vs. 50 [33, 118], p < 0.001), and a significant increase in AC (−8.2 [−14.8, −4.9] vs. -5.8 [−10.1, −3.3], p = 0.003) and mean heart rate (79.8 ± 12.6 vs. 83.9 ± 13.6, p = 0.010). Subgroup analysis indicated similar trends in mean heart rate, DC, AC, and HRV parameters (SDNN, RMSSD, LF, HF, TP) in both the radiotherapy group and the combined treatment group post-radiotherapy. No statistically significant difference was noted in the changes observed in DC, AC, and HRV between the two groups pre- and post-radiotherapy. Conclusion Thoracic radiotherapy may induce cardiovascular autonomic dysfunction by reducing parasympathetic activity and enhancing sympathetic activity. Importantly, the study found that the concurrent use of systemic therapies did not significantly amplify or contribute to the alterations in autonomic function in the short-term following thoracic radiotherapy. DC, AC and HRV are promising and feasible biomarkers for evaluating autonomic dysfunction caused by thoracic radiotherapy.